Relação entre dignidade organizacional e responsabilidade social corporativa na percepção de empregados - Pollon, Vanessa Custodio Zorzetti (2018)
The concept of Corporate Social Responsibility, although widely studied for several decades, still does not present conceptual convergence. In the second decade of the 2000s, the concept of Organizational Dignity emerges, which considers the organization as a generator of decent behavior and actions, thus assigning the term Organizational Dignity to organizations. This study aimed to analyze the relationship between the two constructs, with the purpose of answering the following questions: Can an organization practice Corporate Social Responsibility and not act in a dignified manner towards its stakeholders? Can an organization practice Organizational Dignity and not CSR? This study had an exploratory and quantitative approach, and data were collected electronically, through the application of two scales - the Organizational Dignity Practices (EPRA-DO) scale and the CPCSR Consumer Perception of Corporate Social Responsibility (CPCSR) scale -, to a sample of 214 employees from different companies and segments, whose response data were treated through structural equations. Data analysis revealed that Social Responsibility is a predictor of Organizational Dignity, although constructs are distinct, and the practice of corporate social responsibility brings forth organizational dignity.